2009
DOI: 10.1128/jcm.00321-09
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a New Rapid Antigen Test Using Immunochromatography for Detection of Human Metapneumovirus in Comparison with Real-Time PCR Assay

Abstract: A new rapid human metapneumovirus (hMPV) detection kit using immunochromatography (SAS hMPV test) was compared to real-time PCR for 224 nasal swab specimens, 96.4% of which were obtained from children of <15 years of age. The overall sensitivity and specificity were 82.3% and 93.8%, respectively, suggesting that this test is useful for pediatricians to diagnose hMPV infection in a clinical setting.Human metapneumovirus (hMPV) was first isolated from nasopharyngeal specimens from children with acute respiratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 24 publications
1
28
1
Order By: Relevance
“…In clinical settings, viral antigen detection kits, which are rapid and easy to use, are particularly helpful in making early decisions regarding management and treatment of the patients. Currently, rapid antigen detection test kits are available for influenza viruses, adenoviruses (Ads), and respiratory syncytial virus (RSV), and an immunochromatographic test kit for human metapneumovirus (hMPV) has recently become commercially available in Japan (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…In clinical settings, viral antigen detection kits, which are rapid and easy to use, are particularly helpful in making early decisions regarding management and treatment of the patients. Currently, rapid antigen detection test kits are available for influenza viruses, adenoviruses (Ads), and respiratory syncytial virus (RSV), and an immunochromatographic test kit for human metapneumovirus (hMPV) has recently become commercially available in Japan (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Limitations in rapid antigen testing can be seen with other respiratory viruses, including human metapneumovirus. Although a recent study reported a rapid immunoassay sensitivity and specificity of 82.3 and 93.8%, respectively, for metapneumovirus [27], previous direct antigen detection studies have reported sensitivities ranging from 63.2 to 81% [22,28,29]. The sensitivity of a rapid antigen test is dependent on the reference method with which it is compared.…”
Section: The Evolution Of Diagnostics In Viral Respiratory Infectionsmentioning
confidence: 91%
“…TaqMan real-time PCR was used to detect influenza A virus9, influenza B virus10, respiratory syncytial virus (RSV)11, human metapneumovirus (hMPV)12, norovirus GI/GII13 and dengue virus14. Conventional PCR was used to detect entero/rhinoviruses15 , 16 and chikungunya virus17.…”
Section: Methodsmentioning
confidence: 99%